Kegiatan Berbagi Takjil melalui Program Penyelenggaraan Sedekah untuk Meningkatkan Ketakwaan di Bulan Suci Ramadhan Desa Taman Sepanjang Sidoarjo - Tasya Aulia Rizka (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity is motivated by the suboptimal implementation of sharing values during Ramadan in Taman Sepanjang Village, Sidoarjo, particularly among economically disadvantaged communities who require both material and spiritual support. This study aims to enhance religious awareness, strengthen social solidarity, and empower the community through a takjil-sharing program based on charity. The method used is the Asset Based Community Development (ABCD) approach, consisting of discovery, dream, design, define, and destiny stages. Data collection techniques include participatory observation, interviews, Focus Group Discussions (FGD), and documentation. The results indicate an increase in community understanding of charity and piety, higher participation of residents as volunteers and donors, and stronger social relationships among community members. Furthermore, the program successfully fostered a sustainable culture of sharing and strengthened social cohesion. Despite challenges such as limited funding and coordination, the program is considered effective in providing positive social and spiritual impacts and has the potential for sustainable development.